2007
DOI: 10.1007/s00127-007-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia in Turkish newspapers

Abstract: The attitude of mass media is a strong determinant for stigmatisation since the majority of the society gets exposed to psychiatric disorders via either written or visual media. In this study we explored to demonstrate the meaning attributed to the word schizophrenia in Turkish written printed media. We screened the online sites of 12 national newspapers which allow word scanning between the dates January 1, 2001 and May 1, 2006. The searched terms appeared in a total of 878 texts. In all twelve newspapers, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…On the other hand, a name change would also be welcomed since the inappropriate and metaphoric use of "schizophrenia" or "schizophrenic" made by mass media all over the world (Duckworth et al, 2003;Boke et al, 2007;Clement and Foster, 2008;Magliano et al, 2011), to generically indicate any incoherent/contradictory/deviant behavior, make it difficult to convey its proper meaning and contribute to maintaining the misconceptions and misinformation about the condition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a name change would also be welcomed since the inappropriate and metaphoric use of "schizophrenia" or "schizophrenic" made by mass media all over the world (Duckworth et al, 2003;Boke et al, 2007;Clement and Foster, 2008;Magliano et al, 2011), to generically indicate any incoherent/contradictory/deviant behavior, make it difficult to convey its proper meaning and contribute to maintaining the misconceptions and misinformation about the condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that the names of feared diseases are usually employed with a metaphorical emphasis. In the nineteenth century, for example, metaphors about tuberculosis were very common, while in the twentieth century, these have largely been replaced with metaphors about cancer 4. Over the course of the two periods mentioned above, the use of schizophrenia as a metaphor declined.…”
Section: Discussionmentioning
confidence: 99%
“…The media is the public's primary source of information on mental illness,1-3 and the attitude of the mass media is an important determinant of stigmatization 4. Many researchers have highlighted the role of the media in contributing to the stigma experienced by people with mental illnesses 5.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, Coverdale, Nairn, & Claasen (2002) found that negative depictions and dangerousness to others were present in 61% of print media stories referring to mental illness, and criminality in 47%. Boke et al, (2007) found that 20% of Turkish newspaper stories on schizophrenia featured violence, and Vahabzadeh, Wittenauer, & Carr (2011) found that 60% of human interest stories in US newspapers stories associated schizophrenia with violence, dangerousness, and criminality. In Australia, Francis et al, (2005) found that 16% of non-fiction media stories about schizophrenia associated it with crime.…”
mentioning
confidence: 99%